Intravitreal growth factors in proliferative diabetic retinopathy: correlation with neovascular activity and glycaemic management. Issue 3 (1st March 1997) - Boulton, Mike; Gregor, Zdenek; McLeod, David; Charteris, David; Jarvis-Evans, John; Moriarty, Patrick; Khaliq, Asud; Foreman, David; Allamby, David; Bardsley, Bill
Abstract : AIM: Many growth factors are implicated in proliferative diabetic retinopathy (PDR). It was decided to test the hypothesis that no one factor is predominant but that a regular profile of levels of different growth factors might be operating, and that the profile might differ according to whether or not insulin therapy was part of the patient's glycaemic management. The levels of several growth factors in vitrectomy samples were therefore determined from diabetic patients with tractional, non-haemorrhagic sequelae of PDR and these levels were correlated with (a) each other (growth factor profile), (b) neovascular activity, and (c) the method of glycaemic management (insulin treated (IT) or non-insulin treated (NIT)). METHODS: 72 samples of vitreous were obtained from either diabetic patients with PDR (n = 51) or non-diabetic (control) patients (n = 21). Levels of bFGF, IGF-I, EGF, and insulin were determined by radioimmunoassay; levels of TGF-β2 by ELISA; and levels of IGF-I binding protein by western ligand blotting. The data were analysed using appropriate statistics. RESULTS: There was no regular growth factor profile. bFGF levels were significantly greater in vitreous from NIT patients compared with IT patients and controls. The highest levels of bFGF were found in NIT patients with actively vascularised membranes. TGF-β2 levels were significantly greater in vitreous from IT patients compared with NIT patients and controls The highest levels of TGF-β2 were found in IT patients with actively vascularised membranes. IGF-I levels were significantly greater in diabetics (irrespective of insulin treatment) than non-diabetics and the highest levels of IGF-I were found in IT patients with actively vascularised membranes. A 34 kDa IGFBP was the predominant IGFBP identified in vitreous and was found to be elevated in diabetics patients. CONCLUSION: In PDR there is a correlation between intravitreal growth factor levels and both disease state (whether active or fibrotic) and method of glycaemic management.